Experimental Study on Heat Transfer Characteristics of the Delta Winglets with V-shaped Array - Tian Liting; Gao Yongkun; Wang Jiali; Min Chunhua; Yang Li (Zhileng xuebao)
In the range of Re = 4800~10200, the experiment was made to investigate the heat transfer characteristics of two rows of the delta winglets arrayed in V shape at the back side of the round tube in the rectangular channel. The heat transfer enhancement was compared between the delta winglets with V-shaped array and the single-row large delta winglets, and the effects of attack angle of delta winglet, winglet height and spacing of winglet array were examined. Results show that Nu of the delta winglets with V-shaped array is 4.9% higher than that of the single-row large delta winglets, and the heat transfer in the channel has an increasing trend with the increase of the spacing in winglet array. For the delta winglets with V-shaped array and the single-row large delta winglets, with increasing the attack angle of the delta winglet, the heat transfer enhancement increases firstly and then decreases, and the optimal attack angle is α=60°, while the heat transfer enhancement in both layouts monotonically increases with the increase of the winglet height. The correlations of Nu for the delta winglets with V-shaped array and the single-row large delta winglets are respectively derived by the regression analysis of experimental data. These correlations can be referred for the arrangement of the delta winglets in the fin-and-tube heat exchanger.